2019
DOI: 10.1371/journal.pone.0215291
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biophysical characterization: A screening tool for acetylcholinesterase inhibitors

Abstract: Among neurodegenerative diseases, Alzheimer’s disease (AD) is one of the most grievous disease. The oldest cholinergic hypothesis is used to elevate the level of cognitive impairment and acetylcholinesterase (AChE) comprises the major targeted enzyme in AD. Thus, acetylcholinesterase inhibitors (AChEI) constitutes the essential remedy for the treatment of AD. The study aims to evaluate the interactions between natural molecules and AChE by Surface Plasmon Resonance (SPR). The molecules like alkaloids, polyphen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 58 publications
0
5
1
Order By: Relevance
“…This study showed that the anti-AchE activity of the MeOH extract was higher than that of the other extracts obtained. Indeed, Patil et al [ 63 ] proved that the presence of some phenolic compounds such as Rutin hydrate (with IC 50 = 1.1 × 10 3 μ g/ml) could contribute to the inhibition of AChE. In addition, the present results were better than those found by Ahmad et al [ 62 ] when working with R. hastatus extracts.…”
Section: Resultscontrasting
confidence: 43%
“…This study showed that the anti-AchE activity of the MeOH extract was higher than that of the other extracts obtained. Indeed, Patil et al [ 63 ] proved that the presence of some phenolic compounds such as Rutin hydrate (with IC 50 = 1.1 × 10 3 μ g/ml) could contribute to the inhibition of AChE. In addition, the present results were better than those found by Ahmad et al [ 62 ] when working with R. hastatus extracts.…”
Section: Resultscontrasting
confidence: 43%
“…Belladine 1 and norbelladine 2 (firstly extracted from the Amaryllidaceae family [ 1 ]) are bioactive precursors in the synthesis of drugs acting on the central nervous system, such as galantamine 3 , lycorine 4 , and haemanthamine 5 ( Figure 1 , Panel a) [ 2 , 3 ]. They are natural substances emerging in therapy, showing a cholinesterase inhibitory activity comparable to that of 3 in the treatment of Alzheimer’s disease [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amaryllidaceae is the leading family of genera holding anticholinesterase inhibitors (AChE) activity [12]. In fact, several secondary metabolites such as alkaloids, terpenoids, polyphenols, and quinones and many further compounds from natural sources have been reported as cholinesterase inhibitors [13,14]. For example, alkaloids and flavonoids have been shown to give protection against chronic diseases.…”
Section: Discussionmentioning
confidence: 99%